Inspection activities and tax audit (Discourse of Law and Administration, 2024)
The study aims to demonstrate that the Inspection Activities and Tax Audit, regulated in the Tax Ordinance Act, constitute separate control procedures. These procedures may be undertaken to a different extent by tax authorities in order to verify the correctness of taxpayers’ compliance with the obligations imposed on them by the provisions of tax law obligations. As a result, the taxpayer should (as a rule) submit a corrected tax return to the extent indicated in the tax authority’s control f indings without initiating tax proceedings.
Keywords: inspection activities; tax audit; tax return; corrected tax return